MINAT ANGGOTA KELOMPOKTANI TERHADAP PENERAPAN PLANT GROWTH PROMOTING RHIZOBACTERIA (PGPR) AKAR BAMBU UNTUK TANAMAN CABAI (Capsicum annum L) DI KECAMATAN BANJARAN KABUPATEN BANDUNG - Nurmala Alqisthi Najmudillah; Endang Krisnawati; Nawangwulan Widyastuti (Sekolah Tinggi Pariwisata Mataram, 2020)
Counseling is a process of education outside the school which is systematically organized aimed at adults (the community) so that they are willing, able and self-sufficient in improving or improving the welfare of their families and the wider community. The concept of counseling that will be taken is interest as the participation of a person (farmer) or community group in the development process both in the form of statements and in the form of activities by providing input of thought, energy, time, expertise, capital or material, as well as participating in and enjoying the results. development results. With the negative impact of pesticides, alternative technologies are needed to increase safer agricultural production, namely the use of Plant Growth Promoting Rhizobacteria (PGPR). The analysis used in this thesis research is to use descriptive analysis, the level of interest of chilli farmers in the application of PGPR is analyzed by means of tabulating the data then the average value of the total questions on each indicator item. The assessment of the question is obtained based on the respondent's answer. Then using Simple Regression analysis is a linear relationship between one independent variable (X) and the dependent variable (Y). Then by using Kendall's W Analysis, which is devising a strategy to increase the change in the behavior of chilli farmers' interest in implementing PGPR from the lowest to the highest.